DEVELOPING A SCIENCE TEACHING MODULE BASED ON DIFFERENTIATED LEARNING IN ELEMENTARY SCHOOLS - Aliani; Mulabbiyah; Alwan Mahsul (Auladuna: Jurnal Pendidikan Dasar Islam, 2025)
The purpose of this study is to develop a science and natural sciences (IPAS) teaching module based on differentiated learning on the topic "How is the shape of my Indonesia" that is valid and practical to use in learning activities. This research is a research and development (R&D) with a 4D development model. The study was conducted in class V SDN 1 Terong Tawah with 27 students. Data were collected using an expert validation sheet instrument and a teacher response questionnaire. Based on the results of the validity test, the validity score of the teaching module was in the very valid category. Meanwhile, the results of the practicality test obtained a practicality score of the teaching module in the very practical category. The results of this study indicate that the science and natural sciences teaching module based on differentiated learning has a very high level of validity and practicality, so that it is worthy of being used as an effective and reliable learning tool in supporting the learning process. These findings indicate that the results of the development of the science and natural sciences teaching module based on differentiated learning are useful for improving the quality of learning and can be a reference for the development of innovative teaching tools.